Follistatin like-1 aggravates silica-induced mouse lung injury - Yinshan Fang; Si Zhang; Xiaohe Li; Fangxin Jiang; Qiao Ye; Wen Ning (Scientific Reports)
Abstract Occupational inhalation of dust, such as crystalline silica, for prolonged periods in the workplace leads to fibrotic lung diseases worldwide. The mechanisms underlying the diseases are unknown, so that no effective treatment exists for these conditions. We found elevated levels of follistatin like 1 (FSTL1) in serum from patients with silicosis and in lungs from silica-induced mouse model. The induced Fstl1 regulated inflammation response via activation of nod-like receptor family, pyrin domain containing 3v (NLRP3) inflammasome-mediated IL-1β production from macrophages. Meanwhile, Fstl1 promoted fibrosis via positive regulation of TGF-β1 signaling. Haploinsufficiency of Fstl1 or blockage of FSTL1 with a neutralizing antibody was protective from silica-induced lung injury in mice in vivo. Our data suggest that Fstl1 plays an important role in lung fibrosis, and may serve as a novel therapeutic target for treatment of silicosis.